Between reality and non-reality. Issue 3 (1st November 2021) - Lefa, Nora
Virtual reality is all too often considered as antithetical to reality, the former being an entity fully separated from the latter. Since there has been historically no consensus among philosophers as to what constitutes reality, this article seeks to contribute to the debate on i crucial issue. It argues that reality should be considered as including non-tangible properties and that, from the first-person point of view, virtual reality is part of the reality of each and every one of us. Furthermore, grey zones between reality and virtual reality, that is to say environments in which reality blends with fantasy and highly personal perception of our surroundings are much more common than often assumed. The article claims that architecture is the most powerful foundation for virtual reality and therefore creator of grey zones. Real spaces (such as cafés or streets, and moreover cities) offer experiences more intense than any typical virtual environment and cause the blurring of awareness in which world we are. Virtual reality is an impoverished reality, and attempts to realize it have led to disastrous outcomes. On the contrary, grey zones, partially anchored on the materiality, actually enrich reality with non-tangible qualities, without threatening its authority in our souls and minds.